1997
DOI: 10.1093/oxfordjournals.deafed.a014308
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship Between American Sign Language and English Literacy

Abstract: This article presents the findings of a study of the relationship between American Sign Language (ASL) skills and English literacy among 160 deaf children. Using a specially designed test of ASL to determine three levels of ASL ability, we found that deaf children who attained the higher two levels significantly outperformed children in the lowest ASL ability level in English literacy, regardless of age and IQ. Furthermore, although deaf children with deaf mothers outperformed deaf children of hearing mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
2
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(113 citation statements)
references
References 9 publications
6
98
2
7
Order By: Relevance
“…With respect to the second hypothesis, it was found that native signers of ASL had significantly higher bilingual abilities in ASL and written English, implying that having control of ASL as a native language may act as a bridge to stronger reading abilities. Previous research conducted by Vernon and Koh (1970), Strong and Prinz (1997), and Stuckless and Birch (1966) has shown that deaf children of deaf parents perform significantly better on reading comprehension tests than do deaf children of hearing parents. As a result, deaf children of deaf parents, who are raised in an ASL environment and develop ASL as a native language, have been found to possess stronger reading skills than deaf children raised by hearing parents, who do not develop ASL as a native language.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…With respect to the second hypothesis, it was found that native signers of ASL had significantly higher bilingual abilities in ASL and written English, implying that having control of ASL as a native language may act as a bridge to stronger reading abilities. Previous research conducted by Vernon and Koh (1970), Strong and Prinz (1997), and Stuckless and Birch (1966) has shown that deaf children of deaf parents perform significantly better on reading comprehension tests than do deaf children of hearing parents. As a result, deaf children of deaf parents, who are raised in an ASL environment and develop ASL as a native language, have been found to possess stronger reading skills than deaf children raised by hearing parents, who do not develop ASL as a native language.…”
Section: Discussionmentioning
confidence: 85%
“…By recognizing the importance of communication and the child's communication needs, parents can foster more positive educational outcomes. When comparing deaf children of deaf parents (DoD) and deaf children of hearing parents (DoH), research has found that DoD generally outperform DoH children in future linguistic and academic success related to their ASL abilities (Meadow, 1968;Quigley & Frisini, 1961;Stevenson, 1964;Strong & Prinz, 1997;Stuckless & Birch, 1966).…”
Section: Family Influences On Deaf Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is well in line with the ELU model , which suggests that explicit processing of domain general semantic representations aids language understanding during challenging language conditions. There are also several studies indicating a positive relationship between general sign language skills and comprehension of written texts (Chamberlain & Mayberry, 2008;Freel et al, 2011;Heiling, 1994;Hoffmeister, 2000;Schönström, 2010) or general literacy skills (Strong & Prinz, 1997). The overall picture indicates that general sign language skills, in particular, maintenance of semantic representations in working memory, is of importance in the development of reading comprehension in DHH signing children.…”
Section: Learning To Comprehend Texts As a Sign Language Usermentioning
confidence: 98%
“…Relato de pesquisa lingüística da língua de sinais como suporte para as habilidades de escrita de crianças surdas (STRONG; PRINZ, 1997;WILLIAMS, 1999, RATHMANN, MANN;MORGAN, 2007).…”
Section: Flexão Verbal Na Escrita De Surdosunclassified